KEMBALI BEKERJA SEBAGAI BENTUK JAMINAN KECELAKAAN KERJA PADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJA CABANG MEULABOH - Mairida, Mairida; Iqbal Fahlevi, Muhammad (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The occurrence of work accidents is not something that everyone wants. However, every worker who has a work accident has the view to be able to rise up in every disaster and recover in the sense of the word return to health. Manpower is one of the economic developments that has an important role in all life as a whole, especially the national economy in terms of increasing production power and safety. The number of job opportunities as a driver of the economic life system for the community and is a very abundant field of need. The purpose of this study is to find out if workers are disabled due to work accidents, they have the right to work again through the JKK-RTW program at the Social Security Administration Agency (BPJS). BPJS) Employment Meulaboh branch, this study uses a method that focuses on the reality in the field that is descriptive qualitative. The author wants to reveal real events that occur in the social environment to participants who take part in the return to work program at BPJS Ketenagakerjaan, the meulaboh branch. Qualitative research uses a research process that produces descriptive data from speech and writing from objective behavior. This study can describe the data generated by qualitative research, so this research does not focus on numbers but rather focuses on the process and results. Meulaboh branch of the Social Security Administration (BPJS) for Employment. From the explanation above, the form of social security provided by the government through BPJS Ketenagakerjaan is to protect the rights of workers and not to prevent the decline and level of termination of employment by either party.